Recovery Of Gold From Chloride Containing Solution Using Electrogenerative Method - Roslan, Nurul Ashikin (2017)
The electrogenerative system that was developed as an alternative method to the electrochemical recovery of gold from chloride solution is presented. In this process, a chemical reaction takes place spontaneously since it does not require any external supply of energy. A static batch cell operating in electrogenerative mode is used in gold recovery from chloride solutions. In this present work, a gold chloride solution was used to replace cyanide solution due to its toxicity. Gold chloride solution is also a suitable alternative lixiviants which has stimulated new developments in extraction technology combined with environmental concern.